Guidelines for the management of diabetes services and patients during the COVID‐19 pandemic. Issue 7 (17th May 2020) - Rayman, G.; Lumb, A.; Kennon, B.; Cottrell, C.; Nagi, D.; Page, E.; Voigt, D.; Courtney, H.; Atkins, H.; Platts, J.; Higgins, K.; Dhatariya, K.; et al.
Abstract: The UK National Diabetes Inpatient COVID Response Group was formed at the end of March 2020 to support the provision of diabetes inpatient care during the COVID pandemic. It was formed in response to two emerging needs. First to ensure that basic diabetes services are secured and maintained at a time when there was a call for re‐deployment to support the need for general medical expertise across secondary care services. The second was to provide simple safe diabetes guidelines for use by specialists and non‐specialists treating inpatients with or suspected of COVID‐19 infection. To date the group, comprising UK‐based specialists in diabetes, pharmacy and psychology, have produced two sets of guidelines which will be continually revised as new evidence emerges. It is supported by Diabetes UK, the Association of British Clinical Diabetologists and NHS England. What's new?: Diabetes specialist services help avoid unnecessary admission and readmission of people with diabetes to secondary care facilities and inpatient teams facilitate their care whilst admitted. Clinicians and trainees without diabetes expertise are providing diabetes care during the COVID‐19 pandemic. This Position Statement outlines the need to maintain key elements of specialist diabetes services with a focus on delivering safe inpatient diabetes care. The Position Statement also outlines simple pathways for the management of inpatients with diabetes by admitting teams in secondary care. This Position Statement will be useful to trusts/health boards in redesigning clinical services during the COVID‐19 pandemic and helping ensure that the safe care of people with diabetes.